Cultures of inquiry from epistemology to discourse in sociohistorical research - Hall, John R. (Cambridge University Press, 1999)
Cultures of Inquiry provides an overview of research methodologies in social science, historical and cultural studies. Facing Kant's proposition that pure reason cannot contain social inquiry, John R. Hall uses a method of hermeneutic deconstruction to produce a 'critique of impure reason', thereby charting a 'third path' to knowledge. Inquiries conventionally allocated to science or interpretation, modern or postmodern, he argues, depend upon interconnected methodologies that transcend present-day disciplinary and interdisciplinary boundaries. He identifies four formative discourses and eight methodological practices of inquiry, and explores new possibilities for translation between different types of knowledge. Cultures of Inquiry neither exoticizes academic subcultures nor essentializes Culture as the spirit of academe. Instead, it addresses workaday issues of research via a sociology of knowledge that speaks to controversies concerning how inquiry is and ought to be practiced under conditions of epistemological disjuncture.